2012
DOI: 10.1016/j.envint.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring environmental stress in East Greenland polar bears, 1892–1927 and 1988–2009: What does hair cortisol tell us?

Abstract: Hair sampled from 96 East Greenland polar bears (Ursus maritimus) over the periods 1892–1927 and 1988–2009 was analyzed for cortisol as a proxy to investigate temporal patterns of environmental stress. Cortisol concentration was independent of sex and age, and was found at significantly higher (p < 0.001) concentrations in historical hair samples (1892–1927; n = 8) relative to recent ones (1988–2009; n = 88). In addition, there was a linear time trend in cortisol concentration of the recent samples (p < 0.01),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 91 publications
2
44
1
Order By: Relevance
“…Recently, several studies have provided biological validation in ursids, including grizzly bears [17], [19], polar bears ( Ursus maritimus ) [16], [18], [20], [21], and Asiatic black bears ( Ursus thibetanus ) [22]. Notably, MacBeth [23] found relatively high levels of cortisol in hair from an emaciated grizzly and an emaciated black bear ( Ursus americanus ) compared with 151 other grizzly bears.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have provided biological validation in ursids, including grizzly bears [17], [19], polar bears ( Ursus maritimus ) [16], [18], [20], [21], and Asiatic black bears ( Ursus thibetanus ) [22]. Notably, MacBeth [23] found relatively high levels of cortisol in hair from an emaciated grizzly and an emaciated black bear ( Ursus americanus ) compared with 151 other grizzly bears.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of significant relationships may indicate the concentrations of POPs are such that they are not impacting or influencing cortisol levels. Studies on polar bear cortisol responses to POPs demonstrated a variation in relationships possibly owing to different tissue matrices (Oskam et al 2004;Bechshoft et al 2012aBechshoft et al , 2012b. For example, cortisol and PCBs measured in polar bear hair demonstrated no relationship with organochlorines (OCs) (Bechshoft et al 2012a), despite the negative trends observed between plasma cortisol and OC levels (Oskam et al 2004).…”
Section: Cortisol Associations With Biological and Biochemical Factorsmentioning
confidence: 99%
“…Studies on polar bear cortisol responses to POPs demonstrated a variation in relationships possibly owing to different tissue matrices (Oskam et al 2004;Bechshoft et al 2012aBechshoft et al , 2012b. For example, cortisol and PCBs measured in polar bear hair demonstrated no relationship with organochlorines (OCs) (Bechshoft et al 2012a), despite the negative trends observed between plasma cortisol and OC levels (Oskam et al 2004). Cortisol relationships with biochemical factors were weak and suggest a lack of relationships with the endogenous and exogenous compounds or may point to our sample set not including individuals with high contaminant concentrations or in poor condition to build extremes into the dataset for a trend to be set.…”
Section: Cortisol Associations With Biological and Biochemical Factorsmentioning
confidence: 99%
“…In addition, hair cortisol concentration (HCC) may not be as sensitive to short‐term stress (Ashley et al 2011, Gonzalez‐de‐la‐Vera et al 2011) as are other measures of hypothalamic–pituitary–adrenal activity, such as serum cortisol (Cattet et al 2003), salivary cortisol (Millspaugh et al 2002) or glucocorticoids measured in urine and feces (Hunt and Wasser 2003, Owen et al 2004). Furthermore, hair itself is a relatively stable medium, which can be collected non‐invasively or opportunistically from free‐ranging animals (Macbeth et al 2010, Bechshøft et al 2012), transported and stored at ambient temperature (Jaspers et al 2010, Macbeth et al 2010), and, under optimal conditions, cortisol incorporated into hair may remain detectable for years to centuries (Macbeth et al 2010, Webb et al 2010, Gonzalez‐de‐la‐Vera et al 2011). Recently, techniques for measuring HCC have been refined for use with hair collected from free‐ranging grizzly ( Ursus arctos ; Macbeth et al 2010) and polar bears (Bechshøft et al 2011, 2012).…”
mentioning
confidence: 99%